E-learning Innovation for Generation Z in Higher Education - Susarno, Lamijan Hadi; Dewi, Utari; Khotimah , Khusnul; Sumarno, Alim; Kristanto, Andi; Pramana, Atan; Pradana, Hirnanda Dimas (Journal of Education Technology, 2024)
Research into the development of online learning for the OBE Photo Media Development course to support the implementation of independent campus learning, which the Indonesian Minister of Education and Culture has proclaimed. The purpose of this research is to develop online teaching materials for RPS-based OBE photo media development courses. This development uses the ADDIE development model. Development stages include Analysis, Design, Development, Implementation, and Evaluation. This development produces Online Teaching Materials for the Photo Media Development course that meet the rules and regulations of OBE lesson plan-based teaching materials. The subject of this research is a student of the Education Technology study program of Universitas Negeri Surabaya. Data analysis using interview and questionnaire methods. From the results of the product, validation was carried out by learning design experts, material experts, and media experts to determine the suitability of OBE lesson plan online teaching materials. The results of this research show that after carrying out a feasibility test, the test results obtained by media experts were 91.67% and material experts were 100%. The results of subject tests on Curriculum and Educational Technology students were taken from individual and small group trials. Three students in personal practices and small group trials by six students obtained respective results of 90% and 95%. The feasibility test results show that the online teaching materials based on the OBE lesson plan in the Photo Media Development course are declared feasible.